On the Nature of the Accusative in Finnish - Bielecki, Robert (Lingua Posnaniensis, 2010)
Modern Finnish grammars display a clear tendency to eliminate the category of the accusative entirely, or to limit it only to manifestations which are heterophonic from manifestations of other cases (the nominative and genitive). However, in older grammars (from the first half of the 20th century), the accusative was considered a proper full member of the inventory of Finnish cases. The present paper can be seen as a defense of the former approach to the accusative, because the author believes that the new approach exposes only the paradigmatical aspect of this part of the Finnish language, concealing the syntagmatic aspect. By means of syntagmatic comparison, different types of grammatical neutralizations are brought into view. One of them is especially instructive for the case in question, because it reveals specific properties not only of the accusative, but also of the category of voice in Finnish.